Israiliyyat dalam kitab tafsir Anwar Baidhawi - Mazlan Ibrahim; Ahmed Kamel Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2004)
Islam is a perfect religion which is covered all aspects of human life. In respect to this, al-Quran as kitabullah has been revealed to all mankinds as a guideline in their life which is cover the aspect of aqidah, ibadah, law, akhlaq, history and others. Al-Quran is revealed through mutawatir method and is guaranteed by Allah Almighty from any amendments. However there is exist the mufassiruun who has moulded their interpretations with Israiliyyat. These elements are used whenever the mufassiruun explains about the story of the prophets. As a result of these, the Tafsir Ma’thur is considered very weak. Therefore this article will analyse one of the well-known tafsir which is written in Malay by Syeikh Abd. al-Rauf bin Ali al-Fansuri al-Singkili namely Tafsir Anwar Baidhawi. This tafsir is widely circulated among the students in Indonesia’s and Malaysia’s pondok. The discussion of this book will be devided into three parts. First, the writer will discuss about the background of Syeikh Abd. Al-Rauf bin Ali al-Fansuri al-Singkili. It follows with the introduction of the kitab. Finally the writer will analyse the verses which is influenced by the Israiliyyat. This article comes to the conclusion that a thorough examinations towards the Malay kitab tafsir should be done intensively in order to ensure that the Muslims community are not influenced by the Israilliyyat interpretation